Imaging the pH evolution of an acute kidney injury model by means of iopamidol, a MRI‐CEST pH‐responsive contrast agent. Issue 3 (11th October 2012) - Longo, Dario Livio; Busato, Alice; Lanzardo, Stefania; Antico, Federica; Aime, Silvio
<x xml:space="preserve">Abstract</x> Purpose To investigate in vivo possible pH level alterations following an acute renal failure disease using a MRI‐CEST pH responsive contrast agent. The impact of functional evolution in different renal compartments over time was also investigated. Methods a mouse model of acute kidney injury was obtained by glycerol‐induced rhabdomyolysis. pH maps were obtained using Iopamidol (0.75 g iodine/kg b.w. corresponding to 2.0 mmol/kg) in a control group (n = 3) and in the acute kidney injury group (n = 6) at 1, 3, 7, 14, and 21 days after the damage induction at 7T. Histology assessment of renal damage and blood urea nitrogen levels were compared with pH maps. Results during the acute kidney injury, there was a robust increase of pH values, which peaked after 3 days, compared with the predamage situation. In addition, it was possible to detect changes in contrast detection between the different functional regions of the damaged kidneys. Moreover, a slow restoration of normal pH values was observed three weeks after the glycerol injection. Conclusions pH appears to be a good parameter to assess the early detection of kidney injury as well as it acts as a reporter of the recovery toward the physiologic functionality. Magn Reson Med 70:859–864, 2013. © 2012 Wiley Periodicals, Inc.